2007
DOI: 10.1021/jf070795u
|View full text |Cite
|
Sign up to set email alerts
|

Exudation of Allelopathic Substances in Buckwheat (Fagopyrum esculentum Moench)

Abstract: Root exudates of the common buckwheat, especially phenolic compounds, were studied. Their contents, both in the soil during the growing season and in agar medium during germination, were determined by HPLC and GC-MS. The allelopathic activity of the soil from a buckwheat stand was evaluated, as well. Palmitic acid, squalene, epicatechin, vitexin, a gallic acid derivative, and a quercetin derivative were the main compounds of the agar medium. In the soil, palmitic acid methyl ester, vanillic acid, rutin, a gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 22 publications
0
61
1
1
Order By: Relevance
“…Water extracts from buckwheat grown soil showed significant repressive activity on root elongation of barnyardgrass (Echinochloa crus-galli) and common purslane (Portulaca oleracea), whereas hairy galinsoga, livid amaranth and lettuce remained unaffected (Tominaga and Uezu, 1995;Kalinova et al, 2005). In another study (Kalinova et al, 2007), soil from a buckwheat stand showed significant suppressive activity against lettuce radicle elongation after 3 d. In methanol and boiling water extracts of this soil, several phytotoxic molecules such as a gallic acid derivative, palmitic acid methyl ester, vanillic acid, rutin, and a 4-hydroxyacetophenone derivative were identified. However, it is unclear whether these compounds originated from root exudates, leachates or necrotic parts of buckwheat.…”
Section: Allelopathymentioning
confidence: 89%
“…Water extracts from buckwheat grown soil showed significant repressive activity on root elongation of barnyardgrass (Echinochloa crus-galli) and common purslane (Portulaca oleracea), whereas hairy galinsoga, livid amaranth and lettuce remained unaffected (Tominaga and Uezu, 1995;Kalinova et al, 2005). In another study (Kalinova et al, 2007), soil from a buckwheat stand showed significant suppressive activity against lettuce radicle elongation after 3 d. In methanol and boiling water extracts of this soil, several phytotoxic molecules such as a gallic acid derivative, palmitic acid methyl ester, vanillic acid, rutin, and a 4-hydroxyacetophenone derivative were identified. However, it is unclear whether these compounds originated from root exudates, leachates or necrotic parts of buckwheat.…”
Section: Allelopathymentioning
confidence: 89%
“…The flavan-3-ols seems less abundant among root polyphenols and studied only in some plants Centuria maculosa, Rumex acetosa, Zea mays, Fagopyrum esculentum, Fragaria ananassa and M. domestica (Bais et al 2006;Tolrà et al 2005;Kalinova et al 2007;Tolrà et al 2009;Hoffmann et al 2011Osawa et al 2011. The flavan-3-ols has also been reported to facilitate the expansion of epidermis cells away from Al during root elongation in Cinnamomum camphora (Osawa et al 2011).…”
Section: O or Ri Ig Gi In Na Al L R Re Es Se Ea Ar Rc Ch H A Ar Rt Timentioning
confidence: 99%
“…The root secretes (+) and (-) catechins,but it is (-) catechin which is phytotoxic and accounts for the invasive behavior in the rhizosphere [66][67].The phenolic root exudate of Buckwheat(Fagopyrum esculentum) has been studied using HPLC and GC-MS and palmitic acid methyl ester and a gallic acid derivative have been implicated as the active constituents [68]. Allelopathic properties have also been found among some terpenoids.…”
Section: Herbicidal Plantsmentioning
confidence: 99%